Corporate Resilience During the Covid-19 Pandemic: the Role of ESG Performance and Financial Flexibility - Khrisna Ariyudha, Pande Putu; Rokhim, Rofikoh (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 18 Nomor 1 Tahun 2024DO - 10.24843/MATRIK:JMBK.2024.v18.i01.p01, 2024)
Stocks of substantial ESG firms have been claimed to perform better during crisis periods and consequently serve as an "equity vaccine" for investors. This study explores ESG ratings and financial flexibility's impact on stock performance. We test these hypotheses in the ASEAN-5 setting by assessing the relation between ESG and financial flexibility to stock price resilience in terms of time to recover during 2020 and 2021. The method used in this study is a cross-sectional data regression analysis. In a sample of 142 stocks from 5 countries consisting of Indonesia, Malaysia, Thailand, Philippines, and Singapore, we found that firms with higher ESG ratings had a better stock market performance. They tend to recover faster to achieve their lowest price in 2019. We also discovered that having more cash and liquid assets before Covid-19 doesn't make a company better at dealing with the impacts of the pandemic compared to other companies. Keyword s : ASEAN-5; corporate resilience; covid-19; ESG; financial flexibility